2020
DOI: 10.3389/fncel.2020.00186
|View full text |Cite
|
Sign up to set email alerts
|

In Search of a Dose: The Functional and Molecular Effects of Exercise on Post-stroke Rehabilitation in Rats

Abstract: Although physical exercise has been demonstrated to augment recovery of the post-stroke brain, the question of what level of exercise intensity optimizes neurological outcomes of post-stroke rehabilitation remains unsettled. In this study, we aim to clarify the mechanisms underlying the intensity-dependent effect of exercise on neurologic function, and thereby to help direct the clinical application of exercisebased neurorehabilitation. To do this, we used a well-established rat model of ischemic stroke consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 75 publications
1
34
0
Order By: Relevance
“…Further, in the brain, the p-tau was more prominent in the hippocampus rather than the cortex [ 15 ]. The most recent study demonstrated that mild and intense exercise training for up to 28 days reduced infarct volume and improved brain function in the rat MCAO model [ 14 ]. Interestingly, the levels of tau protein and brain-derived neurotropic factor (BDNF) were higher in the mild aerobic exercise group than the intense training group, which suggests the variability in the effects of exercise on tau-related pathology according to the intensity, type, and duration of exercise [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in the brain, the p-tau was more prominent in the hippocampus rather than the cortex [ 15 ]. The most recent study demonstrated that mild and intense exercise training for up to 28 days reduced infarct volume and improved brain function in the rat MCAO model [ 14 ]. Interestingly, the levels of tau protein and brain-derived neurotropic factor (BDNF) were higher in the mild aerobic exercise group than the intense training group, which suggests the variability in the effects of exercise on tau-related pathology according to the intensity, type, and duration of exercise [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human stroke, reperfusion by thrombolytic drugs produce ischemic penumbra, which is potentially a salvageable area where neural plasticity takes place with rehabilitation [12]. While PIT infarction makes cell apoptosis and clear infarction margins with no penumbra, the reperfusion process followed by occlusion with MCAO could make a penumbra area, mimicking the human ischemic stroke pathophysiology more [13]; a recent study reported that exercise improved the expression of neuroplasticity proteins including tau and brain-derived neurotrophic factor (BDNF) in a MCAO model of rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…As Shown by Linder et al, higher intensity exercise can promote functional recovery and neuroplasticity after stroke [13][14][15]. Other studies have shown that mild exercise can improve neuroprotection and synaptic plasticity after stroke [16]. These conflicting results underscore that exercise intensity is an important determinant of neurological outcomes after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Our study recently suggested that the beneficial effect of intense exercise was not superior than its milder counterpart, thus mild exercise may be adequate and sufficient to elicit neurorehabilitation poststroke. [ 28 ] Our previous study underlined that too early poststroke exercise increased cell stress and expression of pro-inflammatory cytokines, which amplified tissue damage, and suggests that exercise interventions between 24 h and 3 days may optimize rehabilitation benefit. [ 29 ] In addition, Yagita et al .…”
Section: Effect Of Physical Exercise On Neurorehabilitationmentioning
confidence: 99%